1994
DOI: 10.1111/j.1752-1688.1994.tb03349.x
|View full text |Cite
|
Sign up to set email alerts
|

BMP IMPACTS ON WATERSHED RUNOFF, SEDIMENT, AND NUTRIENT YIELDS1

Abstract: To quantify the effectiveness of best management practice (BMP) implementation on runoff, sediment, and nutrient yields from a watershed, the Nomini Creek watershed and water quality monitoring project was initiated in 1985, in Westmoreland County, Virginia. The changes in nonpoint source (NPS) loadings resulting from BMPs were evaluated by comparing selected parameters from data series obtained before, during, and after periods of BMP implementation. The results indicated that the watershed‐averaged curve num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 1 publication
5
34
2
Order By: Relevance
“…Several practices, including the construction of cross banks on access roads, skid trails, and landings; the rapid re-establishment of a vegetation cover on disturbed areas; and improved management of streamside zones and logging debris, have been adopted to reduce erosional impacts and to limit the delivery of sediment to watercourses, to maintain water quality standards (Park et al, 1994;Griffin, 1995;Wallbrink et al, 2002). In the Lake Region of Chile, final harvesting in forestry plantations commonly takes place in the drier months of the year, between October and April.…”
mentioning
confidence: 99%
“…Several practices, including the construction of cross banks on access roads, skid trails, and landings; the rapid re-establishment of a vegetation cover on disturbed areas; and improved management of streamside zones and logging debris, have been adopted to reduce erosional impacts and to limit the delivery of sediment to watercourses, to maintain water quality standards (Park et al, 1994;Griffin, 1995;Wallbrink et al, 2002). In the Lake Region of Chile, final harvesting in forestry plantations commonly takes place in the drier months of the year, between October and April.…”
mentioning
confidence: 99%
“…The central tendency of the regression residuals used to control for natural variability decreased with the implementation of BMPs, and hence the improvement in water quality was likely a result of BMP implementation. In another study evaluating impacts of BMPs in a Virginia stream, Park et al (1994) reported that watershed-scale BMPs reduced runoff curve number, sediment, and nutrient (N and P) concentrations by approximately 5, 20, and 40%, respectively. Edwards et al (1996) also concluded that concentrations of ammonia nitrogen, Kjeldahl nitrogen, and chemical oxygen demand were significantly reduced by watershed BMPs in an Arkansas stream basin.…”
Section: Discussionmentioning
confidence: 97%
“…BMPs assessed in past studies have been shown to reduce nutrient levels in agricultural streams (e.g., [21,[57][58][59][60][61][62]). However, results from our study did not suggest that BMPs were enhancing water quality in the studied streams.…”
Section: Discussionmentioning
confidence: 99%